Resisting Regulation: Conservation, Control, and Controversy over Aboriginal Land and Resource Rights in Eastern Canada, 1880–1930 - Pulla, Siomonn (International Journal of Canadian Studies / Revue internationale d’études canadiennes)

(untitled) (Conseil international d’études canadiennes, 2012)
During the turn of the twentieth century, the land continued to provide the practical, historical, and spiritual basis of distinct cultural practices for Aboriginal peoples in eastern Canada. This was also a time of direct and often intense cultural assaults on Indigenous traditions by state conservation practices and discourses on game preservation. An analysis of historic Aboriginal assertions of sovereignty and effective control in eastern Canada during this period provides an important context that links the current day neo-liberal discourse on “minority rights” and the resulting paradigm of domestication with the Canadian state’s historic policies of aggressive civilization. This analysis ultimately argues that the historic and ongoing project of nation building in Canada is grounded in a complex nation-to-nation framework, with a long history of international diplomacy and good-governance practices that include the involvement of Aboriginal peoples in seeking positive and practical resolutions to their struggles with the state over their land and resource rights.